The novel laws on shareholders’ meetings affecting minority shareholders in Malaysia - Chen, Thim Wai (Future Academy, 2018)
The purpose of this paper is to examine the potential impact of “Written Resolution” and “No Annual General Meeting” concepts on the minority shareholders in a private company. It surveys the state of the law on shareholders’ meeting as a form of corporate governance before the new concepts were introduced by the Companies Act 2016 on 31st January 2017 and compares it with the latter This paper argues that the new concepts should not have been introduced without any protective measures being provided for the minority shareholders in a private company as a matter of good corporate governance. In this respect, references will be made to similar law on the new concepts and safeguards introduced in the Singapore Companies Act and other similar laws in the Commonwealth countries such as Australia. This paper seeks to identify protective measures for law reform purposes. It will also explore potential practical measures being employed and potential problems faced by private companies registered before the coming into force of the Companies Act 2016, where the annual general meetings are part of its corporate governance system.